New Fomula Organic Liquid Fertilizer (Poc Fb) On The Production Of Lettage (Lactuca sativa L) - Samad, Sofyan; A. Mahmud, Shubzan; Haryanto, Sugeng; Abdullah, Hayun (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Lettuce (Lactuca sativa L.) is a vegetable of the world community for salads, fresh vegetables and lettuce leaf juice. The purpose of this study was to determine the growth and production of lettuce plants. Methods: January - April 2021. Farmers' gardens in Gambesi Village, Ternate, North Maluku. Lettuce seed plant material, new formula liquid organic fertilizer (POC FB) and with treatment consisting of: Treatment without new formulation liquid organic fertilizer (POCFB) 1 liter of water/3 polybags (A1), 5 cc of POCFB treatment / 1 liter of water/3 polybags (A2)., POCFB treatment 10 cc/1 liter of water/3 polybags (A3)., POCFB treatment 15 cc/1 liter of water/3 polybags (A4)., POCFB treatment 20 cc/1 liter of water/3 polybags (A5 ). Agronomic parameters include: 1) Lettuce height (cm), 2) lettuce leaf number, 3) Length (cm), 4) Fresh weight of sample (g) with analysis of variance (Anova). The results of the analysis of variance showed that the treatment of POCFB 20 cc/L water/3 polybags (A5) affected all parameters of lettuce observation, age 10 DAP was 5 cm high, at 20 DAP the highest was 9 cm and at 30 DAP the height was 18 cm. Meanwhile, at harvest, the maximum number of lettuce leaves was 6, the longest leaf was 17 cm, and the heaviest sample weight was 118 g when compared to other treatments. Macro and micro elements in POCFB so as to encourage, accelerate the increase in size, length of lettuce.